Upadek czy transformacja? Poglądy nowożytnej historiografii na specyfikę późnoantycznego miasta lewantyńskiego - Kosz, Marcin (Instytut Historyczny Uniwersytetu Wrocławskiego, 2023)
This paper discusses the evolution of modern historiography`s views of the transformation of Levantine poleis during the Byzantine period. The classical opinion connects this issue with a discussion regarding the problem of the curia`s marginalisation. Recently, scholars tend to emphasise evidence supporting a narrative of continuous development of cities and towns.
Keywords: Bizancjum; Lewant; miasto późnoantyczne; historiografia